Process Optimization of Ultrasonic Co-germination for Enriching Black Highland Barley Polyphenols and Analysis of Phenolic Acid Composition - Junling GUO; Jie ZHANG; Wengang ZHANG; Bin DANG; Xijuan YANG (Shipin gongye ke-ji, 2023)
In this study, the single factor experiment and the Box-Behnken response surface method were employed to find the optimum process parameters of ultrasonic co-germination on enriching black highland barley polyphenols, and the differences in phenolic acid composition were compared before and after ultrasonic co-germination treatment on the basis. The results showed that the optimal process parameters were obtained with ultrasonic pretreatment power 350 W at 30 ℃ for 25 min, and germination time 64 h. The total phenolic content of black highland barley (688.84±5.30 mg/100 g DW) was the highest under the conditions. The results for phenolic acids showed that the contents of protocatechuic acid (free and bound), p-hydroxybenzoic acid (free), vanillic acid (free), caffeic acid (free), syringic acid (free) and p-coumaric acid (free) were increased significantly in the main phenolic acids, which was 14.49, 1.54, 4.73, 1.67, 1.46, 3.73 and 11.49 times of the untreated group respectively after germination treatment. The contents of homogentisic acid (bound), caffeic acid (bound), p-coumaric acid (bound) and ferulic acid (bound) were increased significantly after ultrasonic co-germination treatment, which was 39.24, 1.09, 1.60 and 1.13 times of the untreated group respectively. The DPPH-scavenging capacity treated with germination and ultrasonic co-germination increased significantly by 11.66% and 21.55%, respectively. In summary, both treatments were effective means for enriching phenolic substances and improving antioxidant activity in black highland barley, and suitable enrichment methods could be selected according to different phenolic acid monomers and forms. This study could provide the reference for further improving the utilization value of black highland barley.